2020
DOI: 10.1002/1878-0261.12663
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA methylation patterns in the tumor immune microenvironment of metastatic melanoma

Abstract: The presence of immune cells in the tumor microenvironment has been associated with response to immunotherapies across several cancer types, including melanoma. Despite its therapeutic relevance, characterization of the melanoma immune microenvironments remains insufficiently explored. To distinguish the immune microenvironment in a cohort of 180 metastatic melanoma clinical specimens, we developed a method using promoter CpG methylation of immune cell type-specific genes extracted from genome-wide methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 77 publications
(100 reference statements)
2
33
0
Order By: Relevance
“…Top GO terms in the biological process included immune response, inflammatory response, signal transduction, innate immune response and adaptive immune response In addition, all the pathways that were yielded from KEGG analysis were associated with immune response. Consistent with previous studies, our findings verified that immune cells and extracellular matrix play significant roles in building the melanoma microenvironment [19][20][21]. Furthermore, we performed the overall survival analysis of 663 immune-related genes and identified that 600 genes (90.5%) were associated with better outcomes in metastatic melanoma patients.…”
Section: Discussionsupporting
confidence: 90%
“…Top GO terms in the biological process included immune response, inflammatory response, signal transduction, innate immune response and adaptive immune response In addition, all the pathways that were yielded from KEGG analysis were associated with immune response. Consistent with previous studies, our findings verified that immune cells and extracellular matrix play significant roles in building the melanoma microenvironment [19][20][21]. Furthermore, we performed the overall survival analysis of 663 immune-related genes and identified that 600 genes (90.5%) were associated with better outcomes in metastatic melanoma patients.…”
Section: Discussionsupporting
confidence: 90%
“…37 38 In contrast, Mitra et al investigated DNA methylation clusters based on median methylation values of selected immune cell-specific genes in melanoma patients but failed bringing forth an ICI response prediction signature. 25 The superior goal of a successful anticancer therapy is a long-term clinical benefit. Immunotherapy can lead to remarkable responses which can be objectified by imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Moreover, immune cell methylation patterns might serve as prognostic biomarkers in melanoma. 25 Taken together, there is still a lack of reliable biomarkers for the prediction of a successful therapy response after ICI treatment. DNA methylation profiling might be a robust approach for the development of prognostic or even predictive biomarkers in cancer, as so far, there is still a lack of reliable biomarkers for the prediction of a successful therapy response after ICI treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This process is catalyzed by DNA methyltransferase (DNMT) and uses S-adenosyl methionine (SAM) as the methyl group donor (90)(91)(92). In a pan-cancer context, Mitra et al explored and discovered varying levels of CpG methylation of immune celltype-specific genes that are related to patient survival (93). A comprehensive retrospective paper emphasized the importance of clarifying the DNA methylation sites for the development of cancer biomarkers (94).…”
Section: Tme Stress Induces Dna Methylation Of Immune Effector Cellsmentioning
confidence: 99%